Uterine incision on left antero-lateral wall of the uterus due to unrecognised torsion at caesarean section - Papa Dasari; Bhagyashree A Gundagurthi; Priyanka R (Barpeta Obstetrics and Gynaecological Society, 2022)
Torsion of gravid uterus is a rare event and most commonly recognised at caesarean section either prior to incision or after delivery of the fetus. Difficulties are reported regarding its in recognition, predisposing factors and etiology. A 31 years old primigravida with history of primary infertility who conceived by IVF-ET was hospitalised for early onset severe hypertension at 31 weeks. She underwent caesarean section at 37 weeks and a transverse lower segment incision was performed and baby was delivered by vertex. Placenta did not separate for 20 minutes and was found to be morbidly adherent. After manual removal of the placenta and suturing the incision, it was found to be surprising that the incision was on the left anterolateral wall of the uterus. The uterus was torted in clockwise direction for 900at cervico-isthmical junction. On review of the literature we found that the report of change in placental location on USG may give a clue for suspecting torsion gravid uterus pre-operatively and this finding was documented in the case record as per the serial USG monitoring.